Characterisation of the immune repertoire of a humanised transgenic mouse through immunophenotyping and high-throughput sequencing - Richardson, Eve; Binter, Špela; Kosmac, Miha; Ghraichy, Marie; von Niederhäusern, Valentin; Kovaltsuk, Aleksandr; Galson, Jacob D; Trück, Johannes; Kelly, Dominic F; Deane, Charlotte M; Kellam, Paul; Watson, Simon J (eLife, 2023)
Immunoglobulin loci-transgenic animals are widely used in antibody discovery and increasingly in vaccine response modelling. In this study, we phenotypically characterised B-cell populations from the Intelliselect Transgenic mouse (Kymouse) demonstrating full B-cell development competence. Comparison of the naïve B-cell receptor (BCR) repertoires of Kymice BCRs, naïve human, and murine BCR repertoires revealed key differences in germline gene usage and junctional diversification. These differences result in Kymice having CDRH3 length and diversity intermediate between mice and humans. To compare the structural space explored by CDRH3s in each species’ repertoire, we used computational structure prediction to show that Kymouse naïve BCR repertoires are more human-like than mouse-like in their predicted distribution of CDRH3 shape. Our combined sequence and structural analysis indicates that the naïve Kymouse BCR repertoire is diverse with key similarities to human repertoires, while immunophenotyping confirms that selected naïve B cells are able to go through complete development.
Keywords: transgenic mouse; B cell; antibody